Comparative study on thermal cracking characteristics and bio-oil production from different microalgae using Py-GC/MS - Li, Gang; Ji, Fang; Bai, Xue; Zhou, Yuguang; Dong, Renjie; Huang, Zhigang (International Journal of Agricultural and Biological Engineering, 2019)
The yield and chemical composition of pyrolysis products of Chlorella pyrenoidosa and Schizochytrium limacinum were determined using thermogravimetric analyzer (TGA) and pyrolysis-gas chromatographic mass spectrometry (Py-GC/MS) by varying the temperature ranges. After further analysis of the total ion current (TIC) diagrams of Chlorella pyrenoidosa and Schizochytrium limacinum, it was concluded that both the pyrolysis products of each sample were mainly comprised of hydrocarbons, aromatics, fatty acids, nitrogen compounds, PAHs, phenols, etc, however, the relative content of each compound from Chlorella pyrenoidosa and Schizochytrium limacinum was different. The pyrolysis of Chlorella pyrenoidosa and Schizochytrium limacinum at 350°C produced a maximum yield of bio-oil production (44.32% and 60.99%); moreover, Chlorella pyrenoidosa could lead to more pollutants (nitrogen compounds and PAHs) release (2.71%) compared to that of Schizochytrium limacinum (0.7%). Considering the reasonable bio-oil production and minimum release of pollutants, Schizochytrium limacinum was found to be superior for producing biofuel against Chlorella pyrenoidosa.Keywords: microalgae, Chlorella pyrenoidosa, Schizochytrium limacinum, bio-oil production, thermal cracking, Py-GC-MSDOI: 10.25165/j.ijabe.20191201.3628Citation: Li G, Ji F, Bai X, Zhou Y G, Dong R J, Huang Z G. Comparative study on thermal cracking characteristics and bio-oil production from different microalgae using Py-GC/MS. Int J Agric & Biol Eng, 2019; 12(1): 208–213.